About spiders of hazelnut in Piedmont (Bollettino di zoologia agraria e bachicoltura, 2024)
Notes about the species of spiders collected in some hazelnut orchards of Piedmont are given, with some information about the corology and ecology. Forty-nine species belonging to 13 families were collected. One of them, Philodromus buchariKubcova, 2004, is a new record for Italy and eight of them are new records for Piedmont.
Keywords: spiders; agroecosystem; biodiversity; hazelnut orchards